Role of FDFT1 polymorphism for fibrosis progression in patients with chronic hepatitis C. (21st July 2013) - Stättermayer, Albert F.; Rutter, Karoline; Beinhardt, Sandra; Wrba, Fritz; Scherzer, Thomas‐Matthias; Strasser, Michael; Hofer, Harald; Steindl‐Munda, Petra; Trauner, Michael; Ferenci, Peter
Abstract Background In chronic hepatitis C (CHC), steatosis is associated with fibrosis and impaired response to antiviral therapy. Recently, a polymorphism of single nucleotide polymorphism SNP rs2645424 of farnesyl diphosphate farnesyl transferase 1 (FDFT1) was identified in NAFLD/NASH as a possible causal link to steatosis and fibrosis progression. SNP rs738409 in the adiponutrin gene (PNPLA3) is a well described factor for steatosis. This study evaluated the relation of these SNPs on steatosis, fibrosis and treatment response in CHC. Methods The SNPs rs738409478 and rs2645424 were determined by real‐time PCR in 478 patients with CHC (m/f: 314/164; mean age: 44.9 ± 10.7; GT1: 387, GT4: 91) who completed treatment with peg‐IFN‐α‐2a/ribavirin. All had a pretreatment liver biopsy. Steatosis and fibrosis were graded by board‐certified pathologists according to Brunt and METAVIR respectively. Results The distribution of FDFT1 rs2645424 was GG: 186 (38.9%), AG: 222 (46.4%) and AA: 70 (14.6%) and of the rs738409 PNPLA3 allele: CC: 269 (56.3%), CG: 177 (37.0%) and GG: 32 (6.7%). Overall, FDTF1 polymorphism was not linked to the extent of steatosis or fibrosis. However, in patients without steatosis the AA genotype was associated with advanced fibrosis [AA: 8/20 (40.0%), AG: 6/70 (8.5%), GG: 9/57 (16.1%), P = 0.003]. In contrast, the minor PNPLA3 allele was associated with both steatosis and advanced fibrosis (P < 0.001). Both SNPs did not influence treatment response. Conclusion The minor allele in FDFT1 was associated with advanced fibrosis in the non‐steatotic but not in the steatotic subgroup. This may reflect different metabolic pathways in fibrosis progression for steatotic and non‐steatotic patients with CHC.